Caprinula aff. cedrorum (Blanckenhorn, 1890) from the upper Cenomanian of westem Algeria - Fettouma Chikhi Aouimeur (Revista Mexicana de Ciencias Geológicas)
Caprinid facies occur in the upper Cenomanian of Algeria as rich and diverse caprinid associations at the East (Constantinois and Hodna p.p.), already described by Douvillé (1910)… in order to continue, download the full paper in PDF.